Keto Menu–Effect of Ketogenic Menu and Intermittent Fasting on the Biochemical Markers and Body Composition in a Physically Active Man—A Controlled Case Study - Damian Dyńka; Agnieszka Paziewska; Katarzyna Kowalcze (Foods, 2023)
The combination of ketogenic diet (KD) with intermittent fasting (IF) has, for years, aroused a great interest in the scientific world and among healthy lifestyle enthusiasts. Its importance is even greater when the study subjects are physically active individuals. The aim of the study was a determination of the effect of strict calculated ketogenic menu combined with IF and with caloric deficit on the selected biochemical markers and body composition in a 23-year-old man performing strength training. At the same time, we decided to conduct the first so-deeply investigated and controlled case study in this respect. The study protocol included a 13-week-long ketogenic diet with intermittent fasting (of delayed time-restricted eating 16:8 type) and caloric deficit. A detailed menu was designed and was used by the man throughout the whole study duration. A number of blood tests were performed before and after the implemented dietary intervention. Additionally, body composition was determined weekly and the concentrations of glucose and ketone bodies, as well as pulse rate and arterial pressure, were measured daily. The most important changes noted included a significant increase in testosterone and vitamin D concentrations and significant reduction in the HOMA-IR index and concentrations of hepatic enzymes, insulin, glucose, iron, urea, and free triiodothyronine (FT3). Moreover, a significant improvement of body composition occurred (the ratio of total body mass to the adipose and muscular tissue and water mass improved). Favourable changes were also noted in heart rate and arterial pressure values. In view of that, the KD with IF and caloric deficit exerted favourable effects on most biochemical parameters and on body composition and caused an almost twofold increase in serum testosterone concentration.